The The Influence of MSME Marketing Strategies on Business Able to Survive During the Covid 19 Pandemic - Suarniki, Ni Nyoman; Syafril; Fahmi, Muhammad; Fadilah, Neti Rosiana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of MSME marketing strategies on how Business Able to Survive during the Covid-19 pandemic. This research is a quantitative descriptive study using survey and netnograph methods with the Social Network Analysis approach for MSME business people who are members of MSME groups on Facebook and WhatsApp by providing questionnaires via Google form distribution. The basis for sampling is convenience sampling, namely a sampling technique by easily selecting members from the population to be sampled. The data analysis test tool used in this research is SPSS version 21. The research results show that there is a significant relationship and positive correlation between marketing strategy variables and business variables that continue to run during the Covid-19 pandemic. It is hoped that the research will be able to inspire MSME players to continue to organize marketing strategies so that their businesses can still survive even during a pandemic. This research can also be used as a reference for future researchers in researching marketing strategies of business people.